Bacterial assisted degradation of chlorpyrifos: The key role of environmental conditions, trace metals and organic solvents. (1st March 2016) - Khalid, Saira; Hashmi, Imran; Khan, Sher Jamal
Abstract: Wastewater from pesticide industries, agricultural or surface runoff containing pesticides and their residues has adverse environmental impacts. Present study demonstrates effect of petrochemicals and trace metals on chlorpyrifos (CP) biotransformation often released in wastewater of agrochemical industry. Biodegradation was investigated using bacterial strain Pseudomonas kilonensis SRK1 isolated from wastewater spiked with CP. Optimal environmental conditions for CP removal were CFU (306 × 10 6), pH (8); initial CP concentration (150 mg/L) and glucose as additional carbon source. Among various organic solvents (petrochemicals) used in this study toluene has stimulatory effect on CP degradation process using SRK1, contrary to this benzene and phenol negatively inhibited degradation process. Application of metal ions (Cu (II), Fe (II) Zn (II) at low concentration (1 mg/L) took part in biochemical reaction and positively stimulated CP degradation process. Metal ions at high concentrations have inhibitory effect on degradation process. A first order growth model was shown to fit the data. It could be concluded that both type and concentration of metal ions and petrochemicals can affect CP degradation process. Highlights: P. kilonensis metabolized CP at wide range of nutritional and environmental conditions. Hydrolyzing metabolites TCP and TMP were detected. Metal ions have concentration dependent effect on CP degradation. Type and quantity of petrochemicals could affect CP degradation process.